2003
DOI: 10.1002/j.1939-4640.2003.tb02738.x
|View full text |Cite
|
Sign up to set email alerts
|

Intracytoplasmic Spermatid Injection Can Result in the Delivery of Normal Offspring

Abstract: Almost one-third of all patients with nonobstructive azoospermia undergoing testicular sperm extraction (TESE) and intracytoplasmic sperm injection (ICSI) have cancelled cycles due to failure to find spermatozoa. For these patients, every attempt should be made to rescue the cycles by searching for spermatids. In this retrospective study, we report our experience in using elongating (stage Sb2) and elongated (stage Sc and Sd1) spermatids for ICSI. The study included 488 consecutive ICSI and TESE cycles perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 48 publications
2
6
0
Order By: Relevance
“…The offspring born after spermatid intracytoplasmic injection have been reported to be normal (78). This is consistent with those studies that found that methylation patterns in relation to imprinted alleles are already defined at the spermatogonia stage (79,80).…”
Section: Intracytoplasmic Sperm Injectionsupporting
confidence: 85%
“…The offspring born after spermatid intracytoplasmic injection have been reported to be normal (78). This is consistent with those studies that found that methylation patterns in relation to imprinted alleles are already defined at the spermatogonia stage (79,80).…”
Section: Intracytoplasmic Sperm Injectionsupporting
confidence: 85%
“…In the beginning we decided to evaluate elongated spermatid injected oocytes and observed a fertilization rate of 27.9% whereas various studies have reported 24% [48,49] and 71% [50]. Although we had piezoelectrically stimulated the oocytes of patients with elongated spermatids; our data is still similar to non-activated studies.…”
Section: Groupssupporting
confidence: 60%
“…The presence of spermatids is possibly more likely in men with azoospermia, and, although there have been successful outcomes (9,10), the use of spermatids in ICSI-IVF treatment should still be considered experimental (11,12).…”
Section: Discussionmentioning
confidence: 94%